Norman Berry Peake, 1921–2010, a chalk revolutionary. Issue 5 (October 2017) - Gale, Andy
Abstract: A brief biography of the Cretaceous geologist and bookseller Norman Peake is provided, as a late obituary, and to place his work in context. Norman's work on the stratigraphy of the English chalk was truly groundbreaking, in that he pioneered the publication of accurately drawn graphical logs of chalk, which led eventually to the widespread use of chalk lithostratigraphy in correlation and mapping. His important work on the echinoid Echinocorys, mostly never published, is also reviewed and extended.